2019
DOI: 10.1039/c8na00236c
|View full text |Cite
|
Sign up to set email alerts
|

Platinum single-atom adsorption on graphene: a density functional theory study

Abstract: Single-atom catalysis, which utilizes single atoms as active sites, is one of promising ways to enhance the catalytic activity and to reduce the amount of precious metals used. Here by means of density functional theory based thermodynamics we show that the single platinum atoms preferentially adsorb on the substitutional carbon sites at the hydrogen terminated graphene edge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 71 publications
1
17
0
Order By: Relevance
“…6 It has been confirmed that graphene in the first layer does not affect the binding energy of Pt atoms in the second layer. 8 The atomic structures used for the calculations are shown in Figures S8− S12. We optimized the structure and calculated the binding energy defined by…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 It has been confirmed that graphene in the first layer does not affect the binding energy of Pt atoms in the second layer. 8 The atomic structures used for the calculations are shown in Figures S8− S12. We optimized the structure and calculated the binding energy defined by…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…3−5 We have achieved single Pt atoms adsorbed on graphene by plasma sputtering. 6 Because the catalytic activity of a single atom depends largely on its atomic structure, the adsorption structure of Pt atoms has been experimentally 7 and theoretically 8,9 studied. There is a report on the catalytic activity of single Pt atoms adsorbed on the edge of graphene, 10,11 but the atomic arrangement has not been clarified.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Pt attached to a topological defect (5-7-5 member rings) shows a slightly higher binding energy of 2.55 eV (not shown). 30 During the acquisition of a HAADF-STEM image (as shown in Figure 2e, for example), on the order of four million electron impacts are delivered to the Pt atom without inducing any instability and thus, it is likely there is an underlying defect in the graphene acting as a stabilizer.…”
Section: Resultsmentioning
confidence: 99%
“…The DFT calculations in the present paper are carried out using the STATE [34,68] code with norm-conserving pseudopotentials [69]. The plane-wave basis set is used to expand wave functions (charge density) with cutoff energy of 64 Ry (400 Ry).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, more recent HAADF-STEM measurements have even observed single Pt atoms dispersed on undoped [15,16] and nitrogendoped [17] graphene, which show high catalytic activities and CO tolerance. Theoretically, on the other hand, firstprinciples calculations based on density functional theory (DFT) have been performed extensively to clarify the properties of graphene-supported Pt clusters from viewpoints of geometric [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] and magnetic [35][36][37][38][39][40][41][42][43][44] structures, molecular adsorptions [45][46][47][48][49][50], CO tolerance [51][52][53][54], and catalytic reactions such as CO oxidation [55][56][57][58][59][60], decomposition of O 3…”
Section: Introductionmentioning
confidence: 99%